2014
DOI: 10.1371/journal.pone.0108974
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stromal Cell Therapy Affects Lung Inflammation and Tracheal Responsiveness in Guinea Pig Model of COPD

Abstract: The effects of adipose derived stromal cells (ASCs) were evaluated on tracheal responsiveness and biochemical parameters in guinea pigs model of chronic obstructive pulmonary disease (COPD). Thirty six guinea pigs were divided into 6 groups including: Control, COPD, COPD+intratracheal delivery of PBS (COPD+ITPBS), COPD+intravenous delivery of PBS (COPD+IVPBS), COPD+intratracheal delivery of ASCs (COPD+ITASC) and COPD+intravenous injection of ASCs (COPD+IVASC). COPD was induced by exposing animals to cigarette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Total WBC, eosinophils and neutrophils in lung lavage of COPD guinea pigs were also increased [52]. In Table 3, a summary of total and differential WBC in the blood and lung lavage in different animal models of COPD was presented.…”
Section: Inflammatory Cells and Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total WBC, eosinophils and neutrophils in lung lavage of COPD guinea pigs were also increased [52]. In Table 3, a summary of total and differential WBC in the blood and lung lavage in different animal models of COPD was presented.…”
Section: Inflammatory Cells and Mediatorsmentioning
confidence: 99%
“…In addition, Feizpour et al indicated that the level of IL-8 in serum and BAL of guinea pig models of CS-induced COPD, were increased [52]. Inflammatory mediators and cytokines changes in the blood and lung lavage in different animal models of COPD were presented in Table 3.…”
Section: Inflammatory Cells and Mediatorsmentioning
confidence: 99%
“…The AD-MSCs at passage 3 were seeded into 12-well plates at a density of 1 • 10 4 cells per well and cultured for 24 h in DMEM containing antibiotics and 10% FBS, and were then incubated with a differentiation medium consisting of DMEM supplemented with antibiotics, 3% FBS, 250 mM IBMX (Fluka, Switzerland), 1 mM dexamethasone, 5 mM indomethacin, 0.2 mM insulin, 34mM D-pantothenate, and 66 mM biotin. The cells were maintained in this medium for 3 days and then cultured in an adipogenic maintenance medium consisting of DMEM supplemented with 3% FBS, 0.2 mM insulin, 1 mM dexamethasone, 34 mM D-pantothenate, and 66 mM biotin for 9 days (Yu et al, 2011;Feizpour et al, 2014). Adipogenesis was evaluated using the Oil-Red O staining method and photographed (Aguena et al, 2012).…”
Section: Adipogenic Differentiation Of Ad-mscsmentioning
confidence: 99%
“…Then, the cells were incubated with the differentiation medium consisting of DMEM supplemented with antibiotic, 3 % FBS, 250 µM IBMX, 5 µM indomethacin, 0.2 µM insulin, 1 µM dexamethasone, 34 µM d-panthothenate, and 66 µM biotin. The cells were maintained in this medium for 3 days and then cultured for 9 days in adipocyte maintenance medium consisting of DMEM supplemented with 3 % FBS, 0.2 µM insulin, 1 µM dexamethasone, 34 µM d-panthothenate, and 66 µM biotin [18,19]. The level of adipogenesis was evaluated by Oil Red O staining [20,21].…”
Section: Differentiation Of Ascs To Adipocytesmentioning
confidence: 99%